3D hybrid simulations of the interaction of a magnetic cloud with a bow shock. Issue 8 (25th August 2015) - Turc, L.; Fontaine, D.; Savoini, P.; Modolo, R.
Abstract: In this paper, we investigate the interaction of a magnetic cloud (MC) with a planetary bow shock using hybrid simulations. It is the first time to our knowledge that this interaction is studied using kinetic simulations which include self‐consistently both the ion foreshock and the shock wave dynamics. We show that when the shock is in a quasi‐perpendicular configuration, the MC's magnetic structure in the magnetosheath remains similar to that in the solar wind, whereas it is strongly altered downstream of a quasi‐parallel shock. The latter can result in a reversal of the magnetic field north‐south component in some parts of the magnetosheath. We also investigate how the MC affects in turn the outer parts of the planetary environment, i.e., from the foreshock to the magnetopause. We find the following: (i) The decrease of the Alfvén Mach number at the MC's arrival causes an attenuation of the foreshock region because of the weakening of the bow shock. (ii) The foreshock moves along the bow shock's surface, following the rotation of the MC's magnetic field. (iii) Owing to the low plasma beta, asymmetric flows arise inside the magnetosheath, due to the magnetic tension force which accelerates the particles in some parts of the magnetosheath and slows them down in others. (iv) The quasi‐parallel region forms a depression in the shock's surface. Other deformations of the magnetopause and the bow shock are also highlighted. All these effects can contribute to significantly modify the solar wind/magnetosphere coupling during MC events. Key Points: The effects of the bow shock on magnetic clouds' magnetic field is investigated The extent of the alteration of the MC's structure depends on the encountered shock configuration The magnetic cloud causes an attenuation of the foreshock